Natural ventilation for infection control in health-care settings - Atkinson, James; World Health Organization (Geneva : World Health Organization, 2009)
This guideline defines ventilation and then natural ventilation. It explores the design requirements for natural ventilation in the contex t of infection control, describing the basic principles of design, cons truction, operation and maintenance for an effective natural ventilatio n system to control infection in health-care settings.
Includes bibliographical references.
Also available via the World Wide Web.
Keywords: Ventilation; Infection -- Prevention; Health facilities -- Heating and ventilation; Ventilation -- methods; Air -- Microbiology; Infection Control; Health Facilities -- standards; Guideline